Perceived benefits, perceived barriers and self-efficacy towards weight reduction among overweight and obese children in Kedah, Malaysia - Abdul Karim, Wan Mohd Nurussabah; Abu Saad, Hazizi; Zalbahar, Nurzalinda; Mohd Sukri, Nurul Husna (Universiti Putra Malaysia, 2022)
The objective of this study was to identify the psychological factors (perceived barriers to, perceived benefits of, and perceived self-efficacy toward weight reduction) associated with body mass index (BMI) among overweight (OW) and obese children. A cross-sectional survey was carried out among primary school children in Kedah, Malaysia. A multistage randomised cluster sampling technique was used in this study. The socio-demographic data were collected from the parents, and the researchers took anthropometric measurements of the children. A set of validated instruments were used to assess perceived benefits of weight reduction, perceived barriers to weight reduction, perceived self-efficacy in dietary practice and perceived self-efficacy in exercise among the participants. Data were analysed by using SPSS software for Windows Version 25.0. A total of 398 OW and obese children aged 10 and 11 years old (221 boys and 177 girls) were recruited. Based on the socio-demographic data, the father’s educational level was found to be significantly associated with the child’s body mass index (BMI) (2 = 7.873, p = 0.049). There were no significant differences in mean scores for perceived benefits, perceived barriers, and perceived self-efficacy in dietary practice and exercise between the OW and obese groups (p>0.05). However, perceived self-efficacy in exercise was significantly associated with BMI among OW and obese children (p<0.05). Health perceptions and beliefs variables are important and should be included in any future weight management programme among OW and obese children.